The effect of different types of storage solutions on saphenous vein endothelial integrity in diabetic patients undergoing coronary artery bypass grafting - Kamenov Aleksandar; Stojiljković Vladimir; Petrović Aleksandar; Lazarević Milan; Golubović Mlađan; Perić Velimir; Stošić Marija; Radenković Goran; Nikolić Ivan; Petrović Vladimir; Živić Saša; Milić Dragan (Vojnosanitetski Pregled)
Background/Aim. Taking into consideration the justified popularity of total arterial revascularization, the saphenous vein graft (SVG) is still one of the most utilized conduits in coronary artery bypass grafting (CABG). One of the determining factors of this conduit’s durability is its endothelial integrity at the time of surgery. The aim of the study was to investigate the effect of different storage solutions on SVG endothelial integrity in patients with diabetes mellitus (DM) type 2 (T2DM) and non-T2DM patients undergoing CABG. The solutions under evaluation were heparinized saline solution (0.9% NaCl), heparinized autologous whole blood, Bretschneider (histidine-tryptophan-ketoglutarate – HTK) solution, and fresh frozen plasma (FFP) solution. Methods. Forty patients were included in this study and were divided into two groups: group A with 23 T2DM patients and group B with 17 non-T2DM patients. The effects of these solutions were examined by immunohistochemical staining with anti-CD34 antibodies and morphometric comparison in histologic samples of T2DM patients undergoing CABG between July 2021 and September 2022 with samples provided by non-T2DM patients. Results. In this study, the FFP solution showed the most prominent positive effect on the preservation of SVG endothelial integrity, with an average cell integrity preservation of 92.2%. HTK solution was found to be the least effective, with an endothelial cell preservation integrity of 26.77%. There was no marked statistically significant difference in results from groups A and B. There was a noticeable contrast in preserving SVG endothelial integrity between the two patient groups, T2DM and non-T2DM patients, although it was not statistically significant. Conclusion. The storage solution with the most beneficial effect on SVG endothelial integrity preservation was the FFP solution when harvested via the conventional open method in CABG.